Why a painting is like a pizza : a guide to understanding and enjoying modern art - Heller, Nancy (Princeton, N.J. : Princeton University Press, 2002)
Comparing modern art not only to pizzas but also to traditional and childrenUs art, a professor of art history shows readers how people can refine analytical tools they already possess to understand and enjoy even the most unfamiliar paintings and sculptures. 49 color illustrations. 40 halftones.
Exactly what is "abstract" art? -- Why is a painting like a pizza? -- Making aesthetic decisions in art and in daily life -- Paintings that people love to hate -- Bending -- and breaking -- the rules -- New materials, new rules -- Art invades life, and vice versa -- The emotional impact of (some) abstract art -- Commonsense answers to some of the questions most often asked about modern art.
Includes bibliographical references (pages 184-185) and index.
Print version record.
JSTOR
Keywords: Art, Modern -- 20th century; Art appreciation; Art, Modern; Art -- history; Art -- 20e siècle.; Art -- Appréciation.; ART -- History -- General; Art appreciation; Art, Modern; Künste; Analyse; Kunstbetrachtung; Moderne; Kunstbeschouwing; Art, Modern -- 20th century; Art; 20e siècle.; Appréciation de l'art.; Art -- 20th century; 1900-1999